Psychoeducational Film Intervention with Cognitive Behavioral Therapy (CBT) to Enhance Secure Attachment of Students towards Parents - Siti Rahmah Tursina; Firman Firman (Universitas Ahmad Dahlan, 2024)
Separation from parents to study at a boarding school creates a sense of loss, alienation, loneliness, and a weakening of communication with parents among the students (santri). The issues faced by these students are related to attachment patterns, specifically secure attachment. Secure attachment significantly influences the social and emotional development of students, reduces behavioral problems, and alleviates depression. Therefore, this research aims to examine the efficacy of two psychoeducational interventions utilizing films, one with a cognitive-behavioral therapy (CBT) approach and one without a CBT approach, to enhance secure attachment among students towards their parents. This study employs a randomized controlled trial pre-post test design, with a research population of 20 students from Madrasah Tsanawiyah Candung. The participants are randomly divided into two different intervention groups, each consisting of 10 subjects. Data analysis involves the Wilcoxon signed ranks test and Mann-Whitney test. The results indicate a significant improvement in secure attachment among students in both the psychoeducational film intervention with CBT and the psychoeducational film intervention without CBT. However, further analysis reveals that the psychoeducational film intervention with CBT produces a higher increase in self-esteem compared to the intervention without CBT.